Improving Indonesian Language Outcomes Through the Inside Outside Circle Model: Meningkatkan Hasil Pembelajaran Bahasa Indonesia Melalui Model Lingkaran Dalam Luar - Reiza Dwi Yulianto; Reni Guswita; Tri Wera Agrita (Academia Open, 2025)
General Background: Improving learning quality remains a central goal in primary education. Specific Background: Fourth-grade students at SDN 205/II Bangun Harjo demonstrated low engagement and achievement in Indonesian language learning. Knowledge Gap: Limited research has explored the application of interactive learning models such as Inside Outside Circle in enhancing language learning at the elementary level. Aim: This study aims to describe the improvement in learning processes and outcomes using the Inside Outside Circle model. Methods: A Classroom Action Research design was implemented over two cycles, involving 24 students, using observation, tests, and documentation, with both qualitative and quantitative analysis. Results: Findings indicate a significant improvement in both process and outcomes: process scores increased from 58.3% in cycle I to 81.5% in cycle II, while learning outcome scores improved from 66.7% to 87.5%. Novelty: The study highlights the effectiveness of Inside Outside Circle as a cooperative strategy in fostering active learning and improving academic performance in language subjects. Implications: The model can be adopted as a pedagogical innovation to enhance student-centered learning in primary education. Highlights: Improves student engagement through active participation. Enhances learning outcomes in a structured cycle. Demonstrates effective use of cooperative models in language learning. Keywords: Learning Outcomes, Indonesian Language, Inside Outside Circle, Primary Education, Cooperative Learning